Noncontact depth-resolved micro-scale optical coherence elastography of the cornea - Wang, Shang (Biomed Opt Express, 2014)
High-resolution elastographic assessment of the cornea can greatly assist clinical diagnosis and treatment of various ocular diseases. Here, we report on the first noncontact depth-resolved micro-scale optical coherence elastography of the cornea achieved using shear wave imaging optical coherence tomography (SWI-OCT) combined with the spectral analysis of the corneal Lamb wave propagation. This imaging method relies on a focused air-puff device to load the cornea with highly-localized low-pressure short-duration air stream and applies phase-resolved OCT detection to capture the low-amplitude deformation with nano-scale sensitivity. The SWI-OCT system is used here to image the corneal Lamb wave propagation with the frame rate the same as the OCT A-line acquisition speed. Based on the spectral analysis of the corneal temporal deformation profiles, the phase velocity of the Lamb wave is obtained at different depths for the major frequency components, which shows the depthwise distribution of the corneal stiffness related to its structural features. Our pilot experiments on ex vivo rabbit eyes demonstrate the feasibility of this method in depth-resolved micro-scale elastography of the cornea. The assessment of the Lamb wave dispersion is also presented, suggesting the potential for the quantitative measurement of corneal viscoelasticity.